Human Resource Management Development Strategy in Improving Combat Quality and Operational Preparedness of Soldiers in the 116/Gs Infantry Battalion - Tony Firmanto; Mochamad Vrans Romi (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2024)
This research was conducted to determine the extent of the Human Resource Management Development Strategy in Improving Combat Quality and Operational Preparedness of Soldiers in the 116/GS Infantry Battalion. The problem in this research is that the Human Resource Management Development Strategy in Improving Combat Quality and Preparedness of Soldiers is still not optimal due to several inhibiting factors. This research aims to (1) study and analyze in depth the Human Resource Management Development Strategies in Improving Combat Quality and Operational Preparedness of Soldiers, (2) find out the obstacles faced, and (3) identify and analyze efforts to overcome the obstacles. This research used a descriptive analysis method with a qualitative approach, while data collection techniques were observation and interviews, as well as studying documents related to informants from the Battalion Commander and Battalion Soldiers who were selected purposively. The results showed that the Human Resource Management Development Strategy in Improving Combat Quality and Operational Preparedness of Soldiers had not been carried out optimally due to several inhibiting factors, namely (1) a lack of competent personnel, (2) incomplete facilities and infrastructure, (3) insufficient empowerment, and (4) the lack of quotas for attending education. In these obstacles several efforts were made, namely (1) increasing the competence of soldiers, (2) increasing the number of personnel, (2) increasing the understanding of the main tasks and functions, (3) organizing coaching and coordination activities, (4) conducting training, (5) making a scale priority, (6) improving facilities and infrastructure, (7) increasing development of coaching activities that can be carried out, and (8) Mental coaching.